Usefulness of pathological examinations of the central nervous system for monitoring and controlling perinatal lamb mortality. (17th November 2020) - Robertson, S. M.; Boulton, J.; Xie, G.; Neef, A.; Friend, M. A.
Abstract : Correct diagnosis of cause of death is necessary to suggest the most effective management interventions to reduce perinatal lamb mortality. Haemorrhage on the surface of the brain has been used as a field diagnostic tool to allocate lambs to a cause of death category, but the usefulness of this method was unclear. This study aimed to evaluate whether gross pathology was related to neuronal death and whether haemorrhage of the central nervous system (CNS ) was distinct between differing causes of death, enabling indicators to be used in field diagnoses. Lambs dying from natural causes ( n = 64) and from euthanasia ( n = 7) underwent postmortem examination, then the brain and spinal cord were extracted and examined histologically. Histological changes consistent with neuronal death were not detected in any lamb. Haemorrhage of the meninges and/or parenchyma of the CNS occurred in all lambs. The age of the haemorrhage indicated that it occurred near the time of death in most lambs. Dilation of blood vessels varied in severity but appeared to be unrelated to causal diagnosis, severity of subcutaneous oedema, breathing or milk status. Moderate or severe dilation of blood vessels and haemorrhage of the CNS did not occur in all lambs with alternative clear indicators of dystocia and occurred in all death classifications, so it could not be used as diagnostic indicators for classification of cause of death. Dilation and haemorrhage were unrelated to neuronal damage and may have been artefactual. In conclusion, haemorrhage of the CNS was not indicative of neuronal damage and could not be used to distinguish between lambs with clear indicators of differing causes of death, so it is not recommended as a field diagnostic tool.